2019
DOI: 10.1371/journal.pone.0210696
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of chicken anaemia virus in sick chickens in China from 2014 to 2015

Abstract: Chicken anaemia virus (CAV), a member of the genus Gyrovirus, is the etiological agent of chicken infectious anaemia. CAV infects bone marrow-derived cells, resulting in severe anaemia and immunosuppression in young chickens and a compromised immune response in older birds. We investigated the molecular epidemiology of CAV in sick chickens in China from 2014 to 2015 and showed that the CAV-positive rate was 13.30%, in which mixed infection (55.56%) was the main type of infection. We isolated and identified 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Until 2011, chicken anemia virus (CAV) was the only Gyrovirus member identified. From that moment, several novel gyroviruses were characterized in humans and birds [52,53,54]. Partial genome of CAV was found in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…Until 2011, chicken anemia virus (CAV) was the only Gyrovirus member identified. From that moment, several novel gyroviruses were characterized in humans and birds [52,53,54]. Partial genome of CAV was found in the present study.…”
Section: Discussionmentioning
confidence: 50%
“…The molecular epidemiology of CAV had been previously described, and several genotypes of CAV had been determined by phylogenetic analysis ( 15 , 16 , 19 , 29 , 30 ). In this study, phylogenetic analysis using full-length CAV genomic sequences was performed according to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…These amino acid mutations were universal and mainly concentrated in the Cterminal epitope dominant region, which contained abundant antigenic epitopes. In a word, the above regular variations lead to the formation of different evolutionary subbranches of CIAV strains during the transmission route, and also make isolated genetic evolution most similar to Chinese wild strains in recent years [5], and it has certain guiding signi cance to trace the origin of CIAV isolates clustering based on capsid protein in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Since its rst isolation from contaminated vaccines in Japan [2], it has been transmitted worldwide. Epidemiological investigation revealed that CIAV had also been sporadically distributed in different breeder ocks in China in recent years [3][4][5][6]. CIAV was a non-enveloped virus with a single-stranded circular DNA genome [7], which encodes three partially overlapping ORFs, namely VP1, VP2 and VP3.…”
Section: Introductionmentioning
confidence: 99%